Free tissue transfer with the free rectus abdominis flap in high-risk patients above 65 years: a retrospective cohort study - Thomas, Benjamin; Schmidt, Volker-Jürgen; Hirche, Christoph (Journal of plastic, reconstructive & aesthetic surgery, 2019)
Background - Though technically feasible, free tissue transfer carries the risk of perioperative morbidity and mortality in elderly patients. To minimize the operative treatment time and complication rates, we choose the rectus abdominis muscle (RAM) flap. - Methods - Between 2012 and 2017, 34 patients (mean age: 74±7 years, range: 65-89 years) with comorbidities underwent defect reconstruction with a free RAM flap. Recipient-sites were: lower extremity (65%), trunk (18%), upper extremity (12%), and head and neck (6%). - Results - The ASA status was 2 in 11 patients, 3 in 21 patients, and 4 in 2 patients. Twenty patients (59%) received additional vascular surgery. Three patients (9%) underwent simultaneous restoration of fractures. The mean operative time (OT) was 325±75 min. There was no total flap loss. Partial flap loss occurred in one patient (3%). The incidence of surgical and medical complications was 32% and 38%: 11 patients experienced a total of 22 surgical complications, of which 15 were major (requiring additional surgery) and 7 minor (conservative treatment). One patient died postoperatively because of progressive respiratory failure. Prolonged OT was highly associated with hematoma formation requiring re-operation (p=0.01). ASA status was a significant predictor for postoperative critical care monitoring (p=0.03). Reconstruction was successful in 31 out of 34 patients (91%) during a mean follow-up time of 17.7±8.8 months (range: 2-51 months). - Conclusion - The free RAM flap has proven as a reliable and efficient tool in the armamentarium of reconstructive microvascular surgeons with some advantages in the treatment of multimorbid patients older than 65 years.
Gesehen am 14.05.2019